Study on life histroy traits of Stellera chamaejasme provide insights into its control on degraded typical steppe. (1st August 2021) - Guo, Lizhu; Zhao, Huan; Zhai, Xiajie; Wang, Kaili; Liu, Li; Wang, Kun; Huang, Ding
Abstract: The increase of unpalatable Stellera chamaejasme plants has become commonplace in degraded grasslands of China, which can hinder the establishment and growth of palatable plants and have an impact on sustainable development of livestock production. Controlling S. chamaejasme is thus a necessary, yet usually problematic step towards the degraded grassland. Various measures have been implemented to control S. chamaejasme but relatively little is known about the growth and development of S. chamaejasme in degraded grassland. Therefore, focusing on the life history traits of S. chamaejasme can provide theoretical support underpinning its management. In this study, different age classes of S. chamaejasme plants were surveyed and studied from a degraded typical steppe in China, and the variation of the phenotypic traits, biomass increasement, biomass allocation, reserves and nutrient content were described. These analyses could be of great importance in identifying the management practices of S. chamaejasme that are most consistent with the development of S. chamaejasme in degraded grasslands. We found that most of the phenotypic traits and biomass of all organs increased by different patterns with age class. Like many other species, there has been three developmental phases in S. chamaejasme, however, previous researches only focus on the S. chamaejasme in the adult reproductive phase, therefore leading to a delay between the time of S. chamaejasme′s seedling and the time when it begins to establish. Our findings demonstrate that S. chamaejasme mainly distributes the biomass to belowground part (RMF and SMF), which is conducive to the survival of S. chamaejasme on degraded grasslands, making mowing fail to eradicate S. chamaejasme in practice. Partial least squares path modeling suggested that nutrient content (N) played a key role in flowering of S. chamaejasme, but the indirect effect was greater than direct effect. The results from this study highlight that control efforts and the management of S. chamaejasme should not only focus on the S. chamaejasme individual in unreproductive phase, but also on the belowground part of plant in reproductive phase. Highlights: We firstly divided three developmental phases in the growth of S. chamaejasme. Adult S. chamaejasme with bright flowers are noticed, while seedlings are ignored. S. chamaejasme mainly distributes the biomass to the roots, but the least to flowers. For non-chemical method in controlling S. chamaejasme, the focus should be on its belowground part but not the aboveground.